A Back-stress deconvolution method towards modelling of low cycle fatigue behavior of type 316L(N) stainless steel at room temperature. (January 2023) - Kumar Pandey, Durgesh; Kumar Verma, Prashant; Bhattacharyya, Abir; Sarkar, Aritra
Highlights: Back-stress hardening and softening occurs with cycles during LCF of 316L(N) SS. 3 back-stresses are deconvoluted from back-stress-plastic strain hysteresis loops. Each back-stress component operates only after a threshold plastic strain level. Kinematic hardening parameters were predicted from deconvoluted back stresses. Good match between experimental and predicted response is achieved for all cycles. Abstract: A novel back-stress deconvolution method based on nonlinear-kinematic hardening plasticity theory is proposed to determine the minimum number of back-stresses required to model the low cycle fatigue (LCF) hysteresis loops of 316L(N) stainless steel at room temperature. The deconvoluted back-stresses at different threshold plastic strains corroborate that, three back-stresses can simulate the back-stress vs plastic strain response for all cycles at ± 0.6 % strain amplitude. The variation of kinematic hardening parameters with cycles indicates dynamic evolution of material microstructure and gross microstructural heterogeneity during LCF. The simulated stress–strain hysteresis loops show excellent match with the experiments.